حروف الهجاء فواتح السور- أسرارها معناها إعرابها - شكيمة, عبد القادر (جامعة الوادي - university of Eloued, 2022)
Allah opened 29 suras of his book with the letters of the alphabet, which the Arabs had never given before in the opening of their words. This opening would have attracted the searchers for its secrets, meaning and expression; I was one of them. After the research, I concluded that this opening is the ingenuity of the beginning, and the letters that are mentioned are half of the letters of the lexicon in the twenty-nine Suras is the number of letters of the alphabet; they are the most honourable ones and they are read by their names and have provisions in their recitation. Because it did not come from the text of the Messenger of Allah Peace Be Upon Him in the interpretation, the commentators of the Companions and their followers differed in their meaning; the most likely one refers to the miracle of the Holy Quran. In other words, the Arabs were unable to come up with such a Qur'an; it is made of these letters that they speak. Based on the difference in meaning, they differed in their interpretation. Based on the most correct view of its meaning, it is reasonable to say that it is permissible to express it. افتتح الله سبحانه وتعالى تسعا وعشرين سورة من كتابه بحروف الهجاء، وهو ما لم يعهده العرب من قبل في افتتاح كلامهم، فكان هذا الافتتاح من شأنه أن يجذب الباحثين عن البحث عن أسرارها وكنهها ومعناها وإعرابها، فكنت مِن المجذوبين، وخلصت بعد البحث إلى أن هذا الافتتاح من براعة الاستهلال، والحروف التي ذكرت هي نصف حروف المعجم في تسع وعشرين سورة وهي عدد حروف الهجاء، وما ذكر من هذه الحروف هو أشرفها، وتقرأ بأسمائها ولها أحكام في تلاوتها ذكرها أهل التجويد، ولأنه لم يأت نص عن رسول الله صلى الله عليه وسلم في تفسيرها اختلف في معناها المفسرون من الصحابة ومن بعدهم على أقوال كثيرة أرجحها القول الذي يشير إلى إعجاز القرآن الكريم؛ أي ان العرب عجزوا أن يأتوا بمثل هذا القرآن وهو مؤلف من هذه الحروف التي يتكلمون بها، وبناء على الاختلاف في معناها اختلفوا في إعرابها، وبناء على القول الراجح في معناها يترجح القول بأنه لامحل لها من الإعراب .
مقال
Keywords: حروف الهجاء و التجويد المعاني